Causal effects of gut microbiota on erectile dysfunction: a two-sample Mendelian randomization study - Zhang, Yuyang; Chen, Yuxi; Mei, Yangyang; Xu, Renfang; Zhang, Hong; Feng, Xingliang (Frontiers in Microbiology, 2023)
Background Several observational studies have reported the correlation between gut microbiota and the risk of erectile dysfunction (ED). However, the causal association between them remained unestablished owing to intrinsic limitations, confounding factors, and reverse causality. Therefore, the two-sample Mendelian randomization (MR) study was performed to determine the causal effect of gut microbiota on the risk of ED. Methods The MR analysis utilized the publicly available genome-wide association study (GWAS) summary-level data to explore the causal associations between gut microbiota and ED. The gut microbiota data were extracted from the MiBioGen study (N = 18,340), and the ED data were extracted from the IEU Open GWAS (6,175 ED cases and 217,630 controls). The single nucleotide polymorphisms (SNPs) served as instrumental variables (IVs) by two thresholds of P-values, the first P-value setting as <1e-05 (locus-wide significance level) and the second P-value setting as <5e-08 (genome-wide significance level). The inverse variance weighted approach was used as the primary approach for MR analysis, supplemented with the other methods. In addition, sensitivity analyses were performed to evaluate the robustness of the MR results, including Cochran's Q test for heterogeneity, the MR-Egger intercept test for horizontal pleiotropy, the Mendelian randomization pleiotropy residual sum, and outlier (MR-PRESSO) global test for outliers, and the forest test and leave-one-out test for strong influence SNPs. Results Our results presented that the increased abundance of Lachnospiraceae at family level (OR: 1.265, 95% CI: 1.054–1.519), Senegalimassilia (OR: 1.320, 95% CI: 1.064–1.638), Lachnospiraceae NC2004 group (OR: 1.197, 95% CI: 1.018–1.407), Tyzzerella3 (OR: 1.138, 95% CI: 1.017–1.273), and Oscillibacter (OR: 1.201, 95% CI: 1.035–1.393) at genus level may be risk factors for ED, while the increased abundance of Ruminococcaceae UCG013 (OR: 0.770, 95% CI: 0.615–0.965) at genus level may have a protective effect on ED. No heterogeneity or pleiotropy was found based on the previously described set of sensitivity analyses. Conclusion Our MR analysis demonstrated that the gut microbiota had inducing and protective effects on the risk of ED. The results provide clinicians with novel insights into the treatment and prevention of ED in the future. Furthermore, our study also displays novel insights into the pathogenesis of microbiota-mediated ED.